DEVELOPMENT OF VILLAGE ENTERPRISES BASED ON INSIDE-OUT LOGIC BUSINESS STRATEGY WITH DEMATEL DEVELOPMENT TECHNIQUE TO DETERMINE THE OPTIMIZATION OF TOURISM VILLAGE BUSINESS STRATEGY - Fatchurrohman, Mochamad; Shobikin, Shobikin; Elisabeth, Damarsari Ratnasahara (ITB AAS Indonesia Surakarta, 2024)
This study seeks to address key barriers impeding the advancement of tourism villages operated by Village-Owned Enterprises in East Java. It aims to devise efficient strategies for enhancing the management of these tourism villages by employing the Inside-Out Logic Business Strategy. This methodology emphasizes prioritizing obstacles and optimizing decision-making trade-offs. The research methodology integrates Interpretive Structural Modeling (ISM) and DEMATEL techniques in a two-phase hybrid approach. ISM constructs a hierarchical framework of identified barriers, while DEMATEL quantitatively assesses interrelations among factors. The study's sample comprises 350 purposively selected BUMDes overseeing tourism villages in East Java. Findings reveal critical hurdles like stakeholder coordination deficits, inadequate lodging facilities, and community innovation shortcomings as primary obstacles in the tourism village development ecosystem. Factors like limited access and connectivity are notably influenced by these primary barriers. The hierarchical depiction and interplay analysis of these factors offer strategic decision-making insights. This study presents a novel ISM-DEMATEL model that not only pinpoints key hurdles hindering rural tourism progression but also furnishes an evidence-based decision-making instrument for formulating more effective and sustainable policies.